Polymeric Systems for Cancer Immunotherapy: A Review - Le, Thai Minh Duy; Yoon, A-Rum; Thambi, Thavasyappan; Yun, Chae-Ok (Frontiers in Immunology, 2022)
Immunotherapy holds enormous promise to create a new outlook of cancer therapy by eliminating tumors via activation of the immune system. In immunotherapy, polymeric systems play a significant role in improving antitumor efficacy and safety profile. Polymeric systems possess many favorable properties, including magnificent biocompatibility and biodegradability, structural and component diversity, easy and controllable fabrication, and high loading capacity for immune-related substances. These properties allow polymeric systems to perform multiple functions in immunotherapy, such as immune stimulants, modifying and activating T cells, delivery system for immune cargos, or as an artificial antigen-presenting cell. Among diverse immunotherapies, immune checkpoint inhibitors, chimeric antigen receptor (CAR) T cell, and oncolytic virus recently have been dramatically investigated for their remarkable success in clinical trials. In this report, we review the monotherapy status of immune checkpoint inhibitors, CAR-T cell, and oncolytic virus, and their current combination strategies with diverse polymeric systems.